Comparison of the genetic structure of four tilapia strains using mtDNA analyses - Sheng, Haiqing; Stevens, Willem Frans; Yakupitiyage, Amararatne; Little, David C.; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1997)
Mitochondrial DNA (mtDNA) was isolated from four commercial strains of tilapia (Orechromis niloticus): AIT, CHITRALADA, GIFT and UDORN strain hold in the Agricultural and Aquatic System Program (AASP) at AIT. Restriction endonuclease analysis of mtDNA has been carried out to compare genetic structure and characterize differentiation in the four strains. The molecular size of mtDNA of these strains was close to 14500 base pairs. The mtDNA was digested by six hexanucleotide restriction enzymes and analyzed by agarose gel electrophoresis with ethidium bromide staining to reveal the restriction patterns of mtDNA. The results show that the fragment patterns produced by two enzymes (Apa I and Dra I) could be used as genetic markers for identification purposes among the four strains of Orechromis niloticus.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Nile tilapia; Fishes -- Genetics